Human computer interaction via the human hand: a hand model - Kuch, J.J.; Huang, T.S. (Proceedings of 1994 28th Asilomar Conference on Signals, Systems and Computers, 1994)
A new method for building lifelike hand models which articulate in a realistic manner is presented. This method has distinct benefits over previous methods, since the fitting to a particular person's hand is quick, simple and very accurate. Following the calibration process which fits it to a particular person's hand, this hand model can be used in numerous HCI scenarios. Calibration is based on anatomical studies of the human hand and on the specific method of recognition to be employed in the HCI scenarios. The calibration method is done visually and requires only three views of the hand to be modeled. The calibration system is designed to be accurate, to be easy to use and to allow for a short calibration time. These characteristics are all desirable when one is working in the realm of a human computer interfacing.< >